The impact of e-management on the effectiveness of the public service Case Study of National Social Security Fund for Workers, Saida Agency - Mouissat, Amine; Benabou, DJilali (Finance and Business Economies Review, 2022)
The effectiveness of the public service through the application of e-management is achieved through the optimal exploitation of the elements of e-management (computers, software, processes, knowledge makers), while achieving the goals of the public service (Response, Accuracy, Quality of Service, Speed, Transparency). In order to answer the problem of the study and to arrive at more accurate results, we have adopted a main hypothesis, indicating that there is relationship to the impact of the application of e-management elements on the effectiveness of the public service. We designed a two-pronged questionnaire, The first axis concerns the extent to which e-management is implemented by the National Fund for Social Insurance for Workers, of Saida agency, that is answered by the Agency's staff. The second axis relates to the degree of effectiveness of the public service, that is answered by the socially insured, After presenting the data and analyzing it through the SPSS program, we reached the conclusion that the application of e-administration Affects the effectiveness of the services provided by the National Fund for Social Insurance for Workers, Saida Agency